Keseimbangan Pasokan dan Permintaan: Analisis Neraca Beras di Kabupaten Hulu Sungai Utara - Heldawati; Norhalimah; Azwar Saihani; Rachman Fitriannoor (Rawa Sains: Jurnal Sains STIPER Amuntai, 2024)
This research aims to determine the availability and need for rice commodities in Hulu Sungai Utara Regency. The type of data used is quantitative data in the form of time series data for the last 5 years, namely from 2017-2021. The availability of rice by sub-district per year in North Hulu Sungai Regency fluctuates (ups and downs). The area with the highest amount of rice availability is Babirik District, while the lowest amount of rice availability is Paminggir District. Meanwhile, the annual demand for rice according to sub-districts in North Hulu Sungai Regency also fluctuates (ups and downs). Banjang District is a district where the demand for rice is increasing every year. The area with the highest demand for rice is in Central Amuntai District. Meanwhile, the district with the lowest demand for rice is in Paminggir District. Overall, North Hulu Sungai Regency is classified as experiencing a rice surplus. Of the 10 sub-districts in Hulu Sungai Utara Regency, there are 9 sub-districts that experience a rice surplus and 1 sub-district that experiences a rice deficit, namely Paminggir District.